Gamification and game-design elements in native digital magazines: the case of MARCA Plus - González-Díez, Laura (2019)
It is more and more common for media outlets to draw upon elements that are traditionally found in games so as to enhance the interactivity of their product, foment the intake of their informational content, highlight their advertisements or attract a younger audience. This essay aims to present the elements and dynamics of games that are used by the digital magazine It is more and more common for media outlets to draw upon elements that are traditionally found in games so as to enhance the interactivity of their product, encourage the intake of their informational content, highlight their advertisements or attract a younger audience. The results demonstrate the presence of these gaming elements in all of the platforms in which the magazine is offered with a reduced number of games per issue and all of the games being related to the informational content.